What can We Learn from City Marketing Practice? - Kavaratzis, Mihalis (European Spatial Research and Policy, 2009)
It is evident in contemporary urban studies that the interest in city marketing both as a practice within urban centre management and as an academic sub-discipline has accelerated. There remain, however, several issues that need clarification before an agreement can be reached as to the exact effects and potential of city marketing as a tool of economic and socio-cultural development. A particular gap can be noticed between theoretical suggestions on the ways in which marketing should be understood and used within cities and the practical implementation as this can be observed in contemporary cities. A common view on this issue highlights the need for practitioners to follow theoretical ideas but the practice can also be a source of useful lessons that might enrich the theory. This paper investigates marketing and branding practices of two European cities in order to extract from the practice lessons that will support the theoretical development of city marketing and city branding and might contribute towards bridging this gap. The cities investigated are Amsterdam and Budapest, both of which provide valuable insights into the challenges of an effective city marketing implementation.